2019
DOI: 10.3390/ijerph17010146
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Preferences for Traceable Food with Different Functions of Safety Information Attributes: Evidence from a Menu-Based Choice Experiment in China

Abstract: It is of great value to study consumer demand for safe foods in promoting the development of a safe food market system and the reduction of food safety risks, as well as foodborne diseases in China. This paper takes traceable pork as an example and constructs food safety information attributes with ex ante quality verification and ex post traceability. Interactions between safety information attributes and the consumer’s response to cost-driven price changes were investigated for 345 consumers in Wuxi City, Ji… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Unsafe food containing infectious viruses, damaging bacteria, parasites, or chemicals can cause more than 200 diseases, and approximately 3.3 million people worldwide die each year from diarrhea to cancers ( Krishnamurthy, 2020 ). In low- and middle-income countries, unsafe food costs $110 billion a year in lost productivity and healthcare costs ( Hou et al, 2019 ). Also, some researches have confirmed that similar to SARS-CoV-1 and other eight coronaviruses, the SARS-CoV-2 virus is expected to behave similarly at freezing temperatures, which means it could remain contagious under −20°C for up to 2 years ( Rizou et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Unsafe food containing infectious viruses, damaging bacteria, parasites, or chemicals can cause more than 200 diseases, and approximately 3.3 million people worldwide die each year from diarrhea to cancers ( Krishnamurthy, 2020 ). In low- and middle-income countries, unsafe food costs $110 billion a year in lost productivity and healthcare costs ( Hou et al, 2019 ). Also, some researches have confirmed that similar to SARS-CoV-1 and other eight coronaviruses, the SARS-CoV-2 virus is expected to behave similarly at freezing temperatures, which means it could remain contagious under −20°C for up to 2 years ( Rizou et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…By setting menus for the shopping experience, the study collected the alternative choices of participants. Based on a MBC experience auction, the corresponding reactions of consumers when product attributions change are captured (Hou et al, 2020a). Generally, MBC is a complicated procedure and expensive to use (Hou et al, 2020b).…”
Section: Menu-based Choice Experience Methodsmentioning
confidence: 99%
“…WTP can also be estimated with RPL, which limits three disadvantages of MNL by allowing random taste variation and alternative percept patterns, and correcting unobserved factors (Alfnes et al, 2006). Furthermore, since the WTP for the food attributes contributes to the consumer's WTP for a food, a model that can estimate WTP for each attribute's contribution is necessary (Hou et al, 2020a). In empirical research, MVP was used to access the WTP for multiple choices of substitute attributes.…”
Section: Logistics Regression Modelmentioning
confidence: 99%
“…It asks consumers to make a series of trade-offs among a set of choice alternatives of products (each described by a set of attributes -or in our case "food safety cues") and this approach has been widely used in the field of consumer food marketing. Choice experiments are increasingly applied to examine preferences for Chinese consumers (Bai, Zhang, & Jiang, 2013;Hou, Hou, & Wu, 2020;Lee, Lusk, Mirosa, & Oey, 2015;Wu, Hu, & Xiong, 2020;Xu, Yang, & Wu, 2019). Participants are presented with hypothetical product choices that are defined on two attributes at-a-time such that there is a trade-off between them and asked to choose which product they would prefer.…”
Section: Conjoint Analysismentioning
confidence: 99%